Academic mobility for region-building and the creation of a Eurasian identity - Pogorelskaya, Anastasiya M. (European journal of higher education)
Drawing on theoretical discussions on identity construction, the article studies the interrelation between academic mobility and the creation of a common (supranational) identity in the post-Soviet space, which is fragmented by cooperation projects and state-level educational policies. Based on the concept of educational regionalism, the article discusses the idea of common identity creation and regional consolidation through educational integration and academic mobility. The research covers the ways in which academic mobility participants perceive their identity, as well as the prerequisites for and obstacles to common identity creation. A case study based on interviews with staff and alumni of a joint master's programme in Eurasian integration, run by Russian, Kazakhstani and Kyrgyzstani universities, argues in favour of the positive influence of academic mobility on young people's perceptions of their counterparts from other post-Soviet states.